Volume 4: Manufacturing Materials and Metallurgy; Ceramics; Structures and Dynamics; Controls, Diagnostics and Instrumentation; 1997
DOI: 10.1115/97-gt-281
|View full text |Cite
|
Sign up to set email alerts
|

Stall Inception and the Prospects for Active Control in Four High Speed Compressors

Abstract: As part of a European collaborative project, four high speed compressors were tested to investigate the generic features of stall inception in aero-engine type compressors. Tests were run over the full speed range to identify the design and operating parameters which influence the stalling process. A study of data analysis techniques was also conducted in the hope of establishing early warning of stall. The work presented here is intended to relate the physical happenings in the compressor to the signals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Moreover, since mass flow rate is a global measure, it does not provide detailed phenomena or specific regions of stall in data for further analysis. Use of pressure probes in stall detection has been extensively studied and adopted widely in practice [12,13,33]. The probes are located circumferentially within the engine casing to record the pressure oscillation over time.…”
Section: Traditional Stall Detection Methodsmentioning
confidence: 99%
“…Moreover, since mass flow rate is a global measure, it does not provide detailed phenomena or specific regions of stall in data for further analysis. Use of pressure probes in stall detection has been extensively studied and adopted widely in practice [12,13,33]. The probes are located circumferentially within the engine casing to record the pressure oscillation over time.…”
Section: Traditional Stall Detection Methodsmentioning
confidence: 99%
“…Figure 22 clearly shows that there are disturbances originating from the trailing edge of the distortion screen. Lin and Chen [13] and Day et al [19] also reported that the trailing edge of the distortion screen acts as a source of disturbance in the presence of inlet static distortion. However, the long-to-short length scale transition as reported by Lin and Chen [13] was not observed here.…”
Section: Forced Response Of Axial Flow Fanmentioning
confidence: 99%
“…4(a). The sensor location close to the rotor leading edge helps investigate the stall inception mechanism [19,34]. The pressure range of these sensors is 0-2 PSID.…”
Section: Instrumentation and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enforced turbulent eddy flow with unsteady gas pressure oscillation in side channel stages diminishes unsteady gas pressure oscillation in the centrifugal compressor stage and limits pressure gradient as well as the maximum reachable value of gas pressure oscillation at rotating stall. [2], [3], [4], [5] und [6]. Es [14], [15], [16].…”
Section: Introductionmentioning
confidence: 99%